1995
DOI: 10.1006/viro.1995.1441
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies Raised against Covalently Crosslinked Complexes of Human Immunodeficiency Virus Type 1 gp120 and CD4 Receptor Identify a Novel Complex-Dependent Epitope on gp120

Abstract: The binding of the human immunodeficiency virus type 1 (HIV-1) envelope glycoprotein, gp120, to its cell surface receptor, CD4, represents a molecular interaction involving distinct alterations in protein structure. Consequently, the pattern of epitopes presented on the gp120-CD4 complex should differ from those on free gp120. To investigate this concept, mice were immunized with covalently crosslinked complexes of viral HIV-1IIIBgp120 and soluble CD4. Two monoclonal antibodies (MoAbs) obtained from the immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…Human CD4 induces anti-CD4 antibodies that themselves neutralize HIV-1. Indeed, absorption of anti-CD4 antibodies removed some but not all of the crosssubtype neutralizing activity induced by CD4-rgp120 complexes (5,9). Second, CD4, when complexed to rgp120, can be part of a new neutralizing determinant in the complex and/or induce new neutralizing determinants on rgp120 following induction of conformational changes in rgp120 by CD4 (5,6,9).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Human CD4 induces anti-CD4 antibodies that themselves neutralize HIV-1. Indeed, absorption of anti-CD4 antibodies removed some but not all of the crosssubtype neutralizing activity induced by CD4-rgp120 complexes (5,9). Second, CD4, when complexed to rgp120, can be part of a new neutralizing determinant in the complex and/or induce new neutralizing determinants on rgp120 following induction of conformational changes in rgp120 by CD4 (5,6,9).…”
Section: Discussionmentioning
confidence: 98%
“…DeVico et al have shown that expression of CD4-induced neutralizing determinants defined by MAbs raised against CD4-rgp120 complexes vary in their expression on native gp120s, being constitutively expressed on some gp120s and less so on others (5). In this regard, rgp120 89.6 had constitutive low-level expression of MAb 17b (7) binding that increased after MAb A32 binding while rgp120 BaL had no constitutive MAb 17b binding.…”
Section: Discussionmentioning
confidence: 99%
“…Purified soluble human and macaque CD4 (sCD4) was obtained from Biogen (Cambridge, MA). Cross-linked complexes were prepared with HIV BaL gp120 and sCD4 by using bis-sulfosuccinimidyl suberate (Pierce, Rockford, IL) as previously described (35). The rhFLSC was generated from a single-chain HIV BaL gp120-human CD4D1D2 complex (24) by replacing the human D1D2 component with a D1D2 gene fragment from rhesus macaque CD4.…”
Section: Methodsmentioning
confidence: 99%
“…51,76,77,175,176 Attempts have been made by various groups to evaluate such triggered Env (gp120-CD4 complexes) as potential vaccine candidates. 75,177 It was demonstrated that gp120-CD4 complexes can induce broadly neutralizing antibody responses, but they need to be stabilized using cross-linking reagents. 177 In a proof of concept study, we have demonstrated that triggered Env (gp120-CD4 complexes) induced strong immune responses against both gp120 and CD4 101 and these antibodies neutralized both a primary isolate (SF162) as well as a T-cell adapted isolate (SF2).…”
Section: Structural Optimization To Target Conserved Neutralization Ementioning
confidence: 99%
“…75,177 It was demonstrated that gp120-CD4 complexes can induce broadly neutralizing antibody responses, but they need to be stabilized using cross-linking reagents. 177 In a proof of concept study, we have demonstrated that triggered Env (gp120-CD4 complexes) induced strong immune responses against both gp120 and CD4 101 and these antibodies neutralized both a primary isolate (SF162) as well as a T-cell adapted isolate (SF2). 178 To elucidate the contribution of anti-Env antibodies to neutralization, we affinity purified the anti-Env antibodies from anti-CD4 antibodies and showed that these antibodies neutralized two subtype B and one subtype C primary HIV-1 isolates that were tested.…”
Section: Structural Optimization To Target Conserved Neutralization Ementioning
confidence: 99%